Pengaruh Variasi Konsentrasi Ekstrak Daun Jati (Tectona Grandis Linn., F.) Terhadap Sediaan Lip Cream Ekstrak Kulit Buah Naga Merah (Hylocereus Polyrhizus) Sebagai Pewarna Alami - Riska Septriyani; Salsabila Adlina; Nitya Nurul Fadilah (An-Najat, 2023)
Lip cream is one of the lip coloring cosmetic preparations in the form of a cream with a soft, creamy texture, easy to apply, can moisturize lips. The purpose of making lip cream is to know the formulation of a combination of teak leaf extract and red dragon fruit skin as a natural dye in lip cream preparations, effect of difference in concentration on physical properties test, stability test, and hedonic test. Teak leaves (Tectona grandis Linn., f) and red dragon fruit peel waste (Hylocereus polyrhizus) in extract with 96% etanol solvent and citric acid as color stabilizer. Lip cream combination of teak leaf extract and read dragon fruit skin has never been done before, therefore this research was carried out to increase the range of color variation of lip cream preparations. The concentratiob of teak leaf extract used is formula 1 5%, formula 2 9%, and formula 3 13%. The three formulations are evaluated for testing on organoleptic parameters, homogeneity, pH, smear power, cycling test, and hedonic. The results showed that a combination of teak leaf extract and red dragon fruit bark extract can be formulated as a natural dye in lip cream preparations. The most liked formulation in term of aroma, sensation of lips and color is formula 3 but does not meet the requirements, therefore there needs to be an improvement in formula 3.